Bacteria and Nutrients in Fermented Bio-extracts from Aromatic Coconut Husk - Thongsamer, Thunchanok; Sukkhee, Nareerat; Vinitnantharat, Soydoa; Tirachulee, Bundit; Patanachan, Pavinee; Limkuansuwan, Vassanasak (Research on Modern science and Utilizing Technological Innovation Journal (RMUTI Journal), 2025)
This study aimed to analyze the characteristics of bio-extracts from discarded fresh aromatic coconut husk using different microbial seeds, super PD.2 and PD.7 for 30 days. The bio-extracts were analyzed for microbial community and the variation of pH, electrical conductivity, tannin, and nutrient composition. The results showed that the bio-extract using PD.2 predominantly contained Lactobacillales of 80 %, while the bio-extract using PD.7 contained Bacillales of 53 % and Lactobacillales of 24 %. The bio-extract contained macro and micronutrients at levels comparable to soilless plant nutrient formulas, except for nitrogen content. Moreover, tannin was detected in both bio-extracts. Therefore, the bio-extracts from coconut husks may be used in agriculture to improve soil quality. In addition, it contains anti-microbial and beneficial microorganisms.